Self-assembly of a triphenylene-based electron donor molecule on graphene: structural and electronic properties - Rie, Joris de la; Enache, Mihaela; Wang, Qiankun; Lu, Wenbo; Kivala, Milan; Stöhr, Meike (The journal of physical chemistry. C, Energy, materials, and catalysis, 2022)
In this study, we report on the self-assembly of the organic electron donor 2,3,6,7,10,11-hexamethoxytriphenylene (HAT) on graphene grown epitaxially on Ir(111). Using scanning tunneling microscopy and low-energy electron diffraction, we find that a monolayer of HAT assembles in a commensurate close-packed hexagonal network on graphene/Ir(111). X-ray and ultraviolet photoelectron spectroscopy measurements indicate that no charge transfer between the HAT molecules and the graphene/Ir(111) substrate takes place, while the work function decreases slightly. This demonstrates that the HAT/graphene interface is weakly interacting. The fact that the molecules nonetheless form a commensurate network deviates from what is established for adsorption of organic molecules on metallic substrates where commensurate overlayers are mainly observed for strongly interacting systems.
Gesehen am 26.07.2022